2000
DOI: 10.1136/thorax.55.9.780
|View full text |Cite
|
Sign up to set email alerts
|

Salmeterol in paediatric asthma

Abstract: Background-The addition of long acting inhaled 2 agonists is recommended at step 3 of the British guidelines on asthma management but a recent study suggested no additional benefit in children with asthma. Methods-The aim of this study was to compare, in a double blind, three way, crossover study, the eVects of the addition of salmeterol 50 µg bd, salmeterol 100 µg bd, and salbutamol 200 µg qds in asthmatic children who were symptomatic despite treatment with inhaled corticosteroids in a dose of at least 400 µ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…[7] In a study among children with moderate to severe asthma and taking inhaled corticosteroids, salmeterol was significantly more effective at increasing morning peak expiratory flow rates (PEFR) over a 1 month period than salbutamol. [9] Among children with moderate asthma, no additional benefit was seen by the addition of either salmeterol or more beclomethasone to a daily dose of beclomethasone 400μg in children with excellent compliance. [10] A review of 30 double-blind, randomised, controlled trials on the effects of formoterol and salmeterol on lung function in children with asthma concluded that the evidence does not support the use of longacting β 2 -agonists as monotherapy, nor does it support their general use as regular add-on therapy.…”
Section: β 2 -Agonistsmentioning
confidence: 98%
“…[7] In a study among children with moderate to severe asthma and taking inhaled corticosteroids, salmeterol was significantly more effective at increasing morning peak expiratory flow rates (PEFR) over a 1 month period than salbutamol. [9] Among children with moderate asthma, no additional benefit was seen by the addition of either salmeterol or more beclomethasone to a daily dose of beclomethasone 400μg in children with excellent compliance. [10] A review of 30 double-blind, randomised, controlled trials on the effects of formoterol and salmeterol on lung function in children with asthma concluded that the evidence does not support the use of longacting β 2 -agonists as monotherapy, nor does it support their general use as regular add-on therapy.…”
Section: β 2 -Agonistsmentioning
confidence: 98%
“…Although salmeterol 50 micrograms twice daily provides significant improvement in lung function compared with placebo or 'as needed' salbutamol, beclamethasone 400 micrograms per day is more effective than salmeterol. 15 We feel one should consider salmeterol for children receiving optimal inhaled corticosteroid therapy who continue to experience symptoms requiring frequent bronchodilator therapy. Salmeterol should not be used as a rescue medication and its role in long term monotherapy is controversial and unproven.…”
Section: Sodium Cromoglycatementioning
confidence: 99%
“…The author states that the literature was explored with the use of standard search engines and then supplemented by a nonsystematic review. It is unclear why the author included these eight articles and why those by Weinstein et al, 2 Russell et al, 3 and Byrnes et al, 4 as examples, were excluded. Many of the included papers do not define exacerbations or require inhaled corticosteroid use, which the author states was the objective of the study.…”
Section: Letters To the Editormentioning
confidence: 99%